The Migration of Uyghur Turks from East Turkestan - Demirez, Aysun (Bartin University, 2025)
ABSTRACT Throughout world history, large-scale migrations have occurred and continue to occur due to political, economic, religious, and social reasons, as well as natural events, epidemics, and fear for their lives. Migration leads to significant changes in both the history of countries and the lives of people. It also affects literature. Indeed, one of the earliest epics of the Uyghur Turks is the Epic of Migration. From the second half of the 19th century onward, the influence of China, Tsarist Russia, and later the USSR in the Turkestan region influenced the fate of the Turkic people, causing displacement of Turkic communities across a vast area. After East Turkestan was completely occupied by Manchu China in 1884, some of the Uyghur Turks migrated to the Soviet Union to survive. A part of it is also exiled to the Ili Valley. Uyghur migrations continued during the periods of Nationalist China and the Chinese Communist Government. During the Stalin era in the 1930s, there were also reverse migrations to East Turkestan. Uyghur Turks also experienced displacement within the borders of East Turkestan. Today, Uyghurs are diaspora in many countries. In their diaspora countries, they continue to pursue rights and engage in activities to inform the world about the oppression endured in their homeland. Turkey is one of the most preferred countries for Uyghurs in this wave of migration due to shared history, culture, and religion. Uyghurs in Turkey are trying to cope with migration-related problems and build a new life based on the suffering of the past. This study attempts to present the migration of Uyghurs from East Turkestan in chronological order; The diaspora activities of Uyghur Turks in Turkey, their diaspora lives, attitudes and problems were examined; and the findings are shared. Keywords: Uyghur Turks, East Turkestan, migration, diaspora, life in the diaspora.

Dünya tarihinde politik, ekonomik, dini, sosyal sebepler; tabiat olayları, salgın hastalıklar ve can korkuyla büyük göçler yaşanmış ve yaşanmaktadır. Göçler hem ülkelerin tarihinde hem de insanların yaşamlarında büyük değişikliklere yol açar. Edebiyata da tesir eder. Nitekim Uygur Türklerinin ilk destanlarından biri de Göç Destanı’dır. 19.yüzyılın ikinci yarısından sonra Türkistan coğrafyasında Çin, Çarlık Rusyası, sonrasında SSCB, Türk milletinin kaderini etkilemiş, geniş bir coğrafyada Türk topluluklarının yer değişikliklerine sebep olmuştur. Doğu Türkistan’ın 1884’te tamamen Mançu Çin tarafından işgal edilmesiyle Uygur Türklerinin bir bölümü hayatlarını sürdürebilmek için Sovyetler Birliği’ne göç eder. Bir bölümü de İli Vadisi’ne sürülür. Uygurların göçleri Milliyetçi Çin ve Çin Komünist Hükümeti dönemlerinde de devam eder. 1930’lu yıllarda Stalin döneminde Doğu Türkistan’a ters yönlü göçler de görülür. Bir kısmı da Doğu Türkistan sınırları içinde göç etmek zorunda kalır. Uygurlar günümüzde birçok ülkede diasporadırlar. Diaspora oldukları ülkelerde de ana vatanlarında yaşatılan zulmü dünyaya duyurmak üzere hak arayışlarını sürdüren faaliyetler yürütmektedirler. Türkiye, Uygurlar için ortak tarih, kültür, din vb. sebeplerle göç dalgasında en çok tercih edilen ülkelerden biridir. Türkiye’de bulunan Uygurlar hem göçe bağlı sorunlarla baş etmeye hem de geçmişin acıları üzerine yeni bir yaşam kurmaya çalışmaktadırlar. Bu çalışmada Uygurların Doğu Türkistan’dan göçleri tarihsel sırayla verilmeye çalışılmış; Uygur Türklerinin Türkiye’deki diaspora faaliyetleri, diaspora yaşamları, tutumları sorunları irdelenmiş; elde edilen tespitler paylaşılmıştır.
Uygur Türklerinin Doğu Türkistan’dan Göçü
Keywords: South-East (Latest Uyghur/Uzbek) Turkic Dialects and Literatures; Güney-Doğu (Yeni Uygur/Özbek) Türk Lehçeleri ve Edebiyatları